Implementation Of Village Law As A In Implementation Village Government The Community - Widhiyanti, Nur Laily (Faculty of Law, Muhammadiyah University of Surabaya, 2022)
OF6 of 2014 concerning Villages as a guideline for village administration. This research is devoted to understanding in detail the extent to which the village government has implemented the substances contained in the Village Law. This situation is also exacerbated because after the issuance of Law no. 6 of 2014 village government administrators do not really understand the main tasks and functions. The approach to be used in this research is sociolegal. Where this sociolegal approach is not only textual in nature but also sees from the point of view of the impact caused by the existence of the rule itself. The conclusion of this research is that not many village government administrators implement Law no. 6 of 2014 especially in remote villages which tend to be difficult to access existing information. Keywords : Village, Village Government, Village Main Functions.